Polymerase synthesis of DNA labelled with benzylidene cyanoacetamide-based fluorescent molecular rotors: fluorescent light-up probes for DNA-binding proteins - Dziuba, Dmytro; Pohl, Radek; Hocek, Michal (Chemical communications (Cambridge, England), 2015)
Viscosity-sensitive fluorophores, fluorescent molecular rotors based on aminobenzylidene-cyanoacetamide moiety, were tethered to 2'-deoxycytidine triphosphate via a propargylamine linker and incorporated into DNA by polymerases in primer extension, nicking enzyme amplification or PCR. DNA probes incorporating modified nucleosides show a light-up response upon binding to a protein.
Keywords: Protein Binding; DNA-dependentní DNA-polymerasy; Molecular Structure; DNA; benzylidenové deriváty; nitrily; DNA-Binding Proteins; fluorescenční barviva; Aniline Compounds; Fluorescent Dyes; DNA-Directed DNA Polymerase; Benzylidene Compounds; DNA vazebné proteiny; Nitriles; aniliny; molekulární struktura; vazba proteinů